CP110 exhibits novel regulatory activities during centriole assembly in Drosophila. - Franz, A; Roque, H; Saurya, S; Dobbelaere, J; Raff, J (2013)
CP110 is a conserved centriole protein implicated in the regulation of cell division, centriole duplication, and centriole length and in the suppression of ciliogenesis. Surprisingly, we report that mutant flies lacking CP110 (CP110Δ) were viable and fertile and had no obvious defects in cell division, centriole duplication, or cilia formation. We show that CP110 has at least three functions in flies. First, it subtly influences centriole length by counteracting the centriole-elongating activity of several centriole duplication proteins. Specifically, we report that centrioles are ~10% longer than normal in CP110Δ mutants and ~20% shorter when CP110 is overexpressed. Second, CP110 ensures that the centriolar microtubules do not extend beyond the distal end of the centriole, as some centriolar microtubules can be more than 50 times longer than the centriole in the absence of CP110. Finally, and unexpectedly, CP110 suppresses centriole overduplication induced by the overexpression of centriole duplication proteins. These studies identify novel and surprising functions for CP110 in vivo in flies.